2017
DOI: 10.1039/c7ta06504c
|View full text |Cite
|
Sign up to set email alerts
|

A high-efficiency N/P co-doped graphene/CNT@porous carbon hybrid matrix as a cathode host for high performance lithium–sulfur batteries

Abstract: Eco-friendly, multi-heteroatom-doped 3D hybrids were constructed for the first time by one-pot pyrolysis and showed excellent electrochemical performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(77 citation statements)
references
References 42 publications
0
77
0
Order By: Relevance
“…Chen et al synthesized nitrogen, boron co-doped curved graphene nanoribbons (NBCGN) as the carbon precursor and heteroatom sources. Wu et al successfully synthesized an N, P-co-doped 3D carbon hybrid via one-pot pyrolysis process, [35] which owed the 3D interconnected porous frameworks that contributed greatly to the rapid transportation of Li + /e − and suppression of shuttle effect via physical confinement and chemical interaction. They found that N and B co-doping configuration can render the synergistic effect, which produces the NBCGN with larger specific surface area (SSA) and pore volume, better electronic conductivity, enhanced S dispersity, and stronger affinity for LiPSs.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…Chen et al synthesized nitrogen, boron co-doped curved graphene nanoribbons (NBCGN) as the carbon precursor and heteroatom sources. Wu et al successfully synthesized an N, P-co-doped 3D carbon hybrid via one-pot pyrolysis process, [35] which owed the 3D interconnected porous frameworks that contributed greatly to the rapid transportation of Li + /e − and suppression of shuttle effect via physical confinement and chemical interaction. They found that N and B co-doping configuration can render the synergistic effect, which produces the NBCGN with larger specific surface area (SSA) and pore volume, better electronic conductivity, enhanced S dispersity, and stronger affinity for LiPSs.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…The chemical adsorption between host material and Li 2 S 6 polysulfide was also investigated by XPS measurement. As displayed in Figure b and d, the Li 1s spectrum of Co, N−C‐−Li 2 S 6 and Co, N−C@RFC/CNTs−Li 2 S 6 reveal a single symmetric peak at 58.8 and 58.9 eV, corresponding to the Li−N due to the interaction between Li + and N atoms . In addition, the S 2p spectrums of Co, N−C−Li 2 S 6 and Co, N−C@RFC/CNTs−Li 2 S 6 show the three different sulfur environment (Figure c and e), which are assigned to the terminal sulfur atom (S T −1 ), bridging sulfur atom (S 0 B ) and the related thiosulfate or polythionate species, respectively.…”
Section: Resultsmentioning
confidence: 84%
“…A variety of porous carbon/sulfur composite materials have been explored and investigated which exhibited excellent electrochemical performance . In general, porous carbonaceous scaffolds can improve the conductivity of electrode, offer rapid ions/e − transport pathways and physically confine polysulfides through pore structure . Nevertheless, the weak interactions between nonpolar carbon materials and polar sulfur species are insufficient to restrain polysulfides diffusion and shuttle over long‐term cycling, unavoidably resulting in serious capacity fading .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to unique interconnected 3D framework construction, heteroatoms (such as nitrogen, oxygen, boron, and phosphor) [12,13] doping is an effective method to enhance the application properties of the 3D carbon materials for diverse applications and especially for catalytic application. Nitrogen is a well-known electron donating doping atom and nitrogen doping can significantly improve the negative charges mobility on the surface of carbon materials [14][15][16][17] and creates nitrogen vacancies which are beneficial for various kinds of heterogeneous catalytic reaction, direct dehydrogenation of ethylbenzene for example.…”
Section: Introductionmentioning
confidence: 99%